ESTUDANDO MINERAIS 2: O CD ROOM DIDÁTICO “MINERALOGIA: ESTUDAR, ENTENDER E CLASSIFICAR MINERAIS” - Montardo, Doris K.; Klock, Alessandra D.; Traesel, Aline F.; Schneider, Aline; Almeida, Ana P. O. d.; Przyczynski, Carine R.; Weber, Cláudia; Ebert, Clóvis H.; Machado, Daniela d. O. d. L.; Engel, Danieli; et al. (Salão do Conhecimento, 2013)
Resumo